The effectiveness of maternal voice in critically ill children undergoing suctioning with acute pain - Astuti Astuti; Nani Nurhaeni; Fajar Tri Waluyanti; Efa Apriyanti; Juanda Mutifa; Ni Bodro Ardi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Acute pain during suction in pediatric patients in the intensive care unit is unavoidable. However, it is necessary to provide non-pharmacological interventions that nurses can guide. One of the interventions that can applied in that situation is maternal voice. That intervention giving the opportunity to the children hearing the voice of their mother via voice recorder.Objective: This study was conducted to determine the effect of maternal voice on acute pain experienced by critically ill children during suctioning procedure.Methods: The research method used was quasi experiment pretest posttest without control group design. The study was conducted in May-June 2022 in the PICU in one of the hospitals in Jakarta. The research sample was selected by purposive sampling, 21 respondents assessed at the time of pretest and post-test (5 minutes before suctioning procedure, during procedure, and 5 minutes after procedure). The pain of the critically ill children was observed by FLACC (Face, Leg, Activity, Cry, Consolability) Scale.Results: The Saphiro Wilk test of normality data was carried out for all the data, either pretest or post-test data. Bivariate tests were analysed using Wilcoxon Signed Rank Test (for the abnormal data) and Paired T-Test (for the normal data) with the results of pain scores before and after being given maternal voice (when starting suction, p value = 0.001; after starting suction, p value = 0.001; 5 minutes after suction, p value = 0.002).Conclusions: PICU nurses should practice maternal voice along with suction to reduce the pain sensation received by children.